2020
DOI: 10.1210/jendso/bvaa030
|View full text |Cite
|
Sign up to set email alerts
|

Novel CYP19A1 Mutations Extend the Genotype-Phenotype Correlation and Reveal the Impact on Ovarian Function

Abstract: Context The steroidogenic enzyme aromatase (CYP19A1) is required for estrogen biosynthesis from androgen precursors in the ovary and extragonadal tissues. The role of aromatase, and thus estrogens, is best illustrated by genetic variations of the CYP19A1 gene leading to aromatase deficiency or excess. Objective The objective of this work is to characterize novel CYP19A1 variants. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 70 publications
1
9
0
Order By: Relevance
“…The results of the present study demonstrate that estrogens play no role on the ovary/testis determinism of the rabbit gonad. A similar finding had already been described in humans, where several cases of total CYP19A1 gene inactivation were reported (Akcurin et al 2016; Zhu et al 2016; Mazen et al 2017; Unal et al 2018; Praveen et al 2020). In spite of numerous symptoms affecting the development of gonads, of external genitalia and of breast in the girl, with multiple disorders in energy and bone metabolisms, there was no sex reversal of the human ovary as regard to the genetic sex (Zhu et al 2016).…”
Section: Discussionsupporting
confidence: 87%
“…The results of the present study demonstrate that estrogens play no role on the ovary/testis determinism of the rabbit gonad. A similar finding had already been described in humans, where several cases of total CYP19A1 gene inactivation were reported (Akcurin et al 2016; Zhu et al 2016; Mazen et al 2017; Unal et al 2018; Praveen et al 2020). In spite of numerous symptoms affecting the development of gonads, of external genitalia and of breast in the girl, with multiple disorders in energy and bone metabolisms, there was no sex reversal of the human ovary as regard to the genetic sex (Zhu et al 2016).…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, the patient may present with primary amenorrhea (i.e., hypergonadotropic hypogonadism) and mild virilization. Recently, Praveen et al [159] pointed out that although aromatase deficiency generally manifests at birth in females, the diagnosis may also be made later, either by abnormal pubertal development or by ovarian torsion due to (poly)cystic ovaries.…”
Section: Aromatase Deficiency (P450arom)mentioning
confidence: 99%
“…It was found that normal aromatase activity is essential for the proper development of ovarian follicles during fetal development, their maturation, and during ovulation in the reproductive period. A deficiency of aromatase in most cases leads to the development of a polycystic ovary phenotype [ 12 ]. The CYP19A1 rs700518 polymorphism is based on the conversion of adenine (A) to guanine (G) and is one of the most widely studied polymorphisms in relation to bone mineral density (BMD) and osteoporosis.…”
Section: Discussionmentioning
confidence: 99%